2001
DOI: 10.1016/s0014-5793(01)02111-1
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐insensitive phosphoenzyme intermediate of sarcoplasmic reticulum Ca2+‐ATPase has a compact conformation resistant to proteinase K, V8 protease and trypsin

Abstract: Sarcoplasmic reticulum Ca 2+ -ATPase was digested with proteinase K, V8 protease and trypsin in the absence of Ca 2+ . Unphosphorylated enzyme was rapidly degraded. In contrast, ADP-insensitive phosphoenzyme formed with P i and phosphorylated state analogues produced by the binding of F 3 or orthovanadate, were almost completely resistant to the proteolysis except for tryptic cleavage at the T1 site (Arg 505 ). The results indicate that the phosphoenzyme and its analogues have a very compact form in the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 42 publications
(57 reference statements)
8
74
0
Order By: Relevance
“…Proteolysis-SR vesicles (0.45 mg/ml) were digested at 25°C with proteinase K (0.05 mg/ml) or trypsin (0.1 mg/ml) as described previously (10,11) in a buffer containing 50 mM LiCl, 2 mM EGTA, and 50 mM MES/Tris (pH 6). When possible effects of TG or K ϩ on the digestion rate were examined, 4 M TG or 100 mM KCl (in place of LiCl) was included in the above buffer.…”
Section: Preparation Of Sr Vesicles and Treatment With Bef Mgf Alfmentioning
confidence: 99%
See 3 more Smart Citations
“…Proteolysis-SR vesicles (0.45 mg/ml) were digested at 25°C with proteinase K (0.05 mg/ml) or trypsin (0.1 mg/ml) as described previously (10,11) in a buffer containing 50 mM LiCl, 2 mM EGTA, and 50 mM MES/Tris (pH 6). When possible effects of TG or K ϩ on the digestion rate were examined, 4 M TG or 100 mM KCl (in place of LiCl) was included in the above buffer.…”
Section: Preparation Of Sr Vesicles and Treatment With Bef Mgf Alfmentioning
confidence: 99%
“…When possible effects of TG or K ϩ on the digestion rate were examined, 4 M TG or 100 mM KCl (in place of LiCl) was included in the above buffer. The digested samples were subjected to Laemmli SDS-polyacrylamide gel electrophoresis (29), and the densitometric analyses of the gels stained with Coomassie Brilliant Blue R-250 were performed as described previously (10,11). The rate constant for the degradation of a 110-kDa ATPase chain by proteinase K and that for the cleavage at T2 site (Arg 198 ) by trypsin were obtained from the time courses (0 -60 min) by least squares fit as described (11).…”
Section: Preparation Of Sr Vesicles and Treatment With Bef Mgf Alfmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling of tubular crystals formed with decavanadate (E2V) revealed (5) that three cytoplasmic domains gather to form a most compactly organized single headpiece in E2V. With the limited proteolysis experiments, we previously showed (7,8) that E2V is very similar to E2P in domain organization and that E2P is the intermediate having the most compactly organized headpiece in the catalytic cycle. The results further indicated that a large rotation of A domain (by ϳ90° (5)) and its strong association with P and N domains most likely occur during the E1P to E2P transition and suggested that stabilization energy provided by intimate contacts between all three cytoplasmic domains in E2P will provide energy for moving transmembrane helices and release the bound Ca 2ϩ ions.…”
mentioning
confidence: 99%